Detection, scoring and volume assessment of bone erosions by ultrasonography in rheumatoid arthritis: comparison with CT. Issue 4 (15th May 2012) - Døhn, Uffe Møller; Terslev, Lene; Szkudlarek, Marcin; Hansen, Michael Sejer; Hetland, Merete Lund; Hansen, Annette; Madsen, Ole Rintek; Hasselquist, Maria; Møller, Jakob; Østergaard, Mikkel
Abstract : Objectives: To determine the accuracy of ultrasonography (US) for bone erosion detection in different areas of rheumatoid arthritis (RA) metacarpophalangeal (MCP) joints with multislice CT as the reference method. Second, to establish the necessary bone volume loss on CT for US to reliably detect it as an erosion, and finally to compare two semiquantitative US-erosion scoring methods. Methods: The 2nd–5th MCP joints of 49 patients with RA were examined by CT and US, and evaluated for the presence of bone erosion in each MCP joint quadrant. On CT, erosion volume was scored according to the OMERACT-RAMRIS score (bone volume loss in 10% increments of original bone volume). US erosions were scored 0–3 according to the Szkudlarek and Scoring by UltraSound Structural erosion (ScUSSe) systems, respectively. Results: Seven hundred and eighty-four MCP joint quadrants were examined. Erosions were detected by CT in 259 quadrants and by US in 142 quadrants. Sensitivity/specificity/accuracy of US was overall 44%/95%/78% compared with 71%/95%/90% in areas with good US accessibility (radial 2nd MCP, ulnar 5th MCP and all dorsal/palmar aspects). US detected 95% of erosions with bone volume loss >20%. In US accessible areas, 63% of erosions with 1–10% bone volume loss and 94% of erosions with >10% bone loss were detected. The two US scoring systems agreed well on large erosions, whereas the smallest erosions (Szkudlarek grade 1, of which 86% were confirmed by CT) were not scored by ScUSSe. Conclusion: In accessible areas, US was highly accurate for detection and semiquantitative assessment of RA bone erosion. Even the smallest erosions, only detected in one plane, were generally confirmed by CT.